The Association of Thyroid Hormones with Coronary Atherosclerotic Severity in Euthyroid Patients - Yu, Na; Wang, Linjie; Zeng, Yong; Zhao, Yuxing; Chen, Shi; Pan, Hui; Gong, Fengying; Zhu, Huijuan (Hormone and Metabolic Research, 2022)
The aim of the work was to explore the correlation between thyroid hormones and coronary atherosclerotic severity. This cross-sectional study included 340 euthyroid patients who underwent diagnostic coronary artery angiography (CAG). Gensini Score (GS) was applied to assess the severity of coronary atherosclerosis. Thyroid hormones and routine biochemical parameters were measured. The associations between thyroid hormones and coronary atherosclerosis severity were analyzed. Thyroid hormones levels or parameters were taken as both continuous variables and tertiles into analysis, and the lowest tertile was usually used as the reference (OR=1) for medium and highest tertiles. Free triiodothyronine (FT3) level was associated with GS≥22 (Median GS) in Model I adjusted for age and sex [Continuous: OR=0.46, 95% CI (0.23, 0.92), p=0.029; Tertile 3: OR=0.54, 95% CI (0.30, 0.97), p=0.038], and Model II adjusted for all known risk factors of coronary artery disease (CAD) [Continuous: OR=0.44, 95% CI (0.20, 0.95), p=0.036; Tertile 3: OR=0.49, 95% CI (0.25, 0.96), p=0.039]. Subjects with highest tertile of FT3 to free thyroxine (FT4) ratio (FT3/FT4 ratio) appeared to have the remarkably decreased risk of CAD in both Non-adjusted Model [OR=0.49, 95% CI (0.24, 0.98), p=0.044] and Model I [OR=0.45, 95% CI (0.22, 0.93), p=0.031]. Higher FT3 level within normal range was independently and negatively associated with severity of coronary atherosclerosis. Besides, FT3/FT4 ratio was remarkably correlated with the prevalence of CAD in euthyroid population.
Keywords: coronary artery disease; Gensini score; free triiodothyronine; FT3/FT4 ratio; euthyroid